PENGARUH LOKASI, BRAND IMAGE, DAN KERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI WARCET MAS GIMBAL PONOROGO - Palupi, Elfira; Pujianto, Agung; Maduwinarti, Ayun (Universitas 17 Agustus 1945 Surabaya, 2020)
A businessman should be able to think creatively about how to create various products that are different from the other and how to build a good perspective of the product to the consumer. By considering the location factors which are not just strategic but also accessible, easy to recognize and one of the examples is a culinary business. Nowadays, business competition became tighter and the company should pay attention to anything that is could influence consumer judgment when a buy a product. This research tries to explain the significance of the location factor, brand image and product variations toward a consumer purchasing decision. Such as in Warcet Mas Gimbal. Warcet Mas Gimbal is located at Kh. Ahmad Dahlan Kec. Ponorogo Kab. Ponorogo. This research uses quantitative with survey and questionnaire as an instrument. The population in this research were all the consumer who is already visited at the Warcet Mas Gimbal Ponorogo. The data of research use non-probability sampling. By using a purposive sampling technique among 100 respondents. The data were analyzed using multiple linear regression techniques.The result of the research shows, all independent variables that are location, brand image, and product diversity are having a positive impact on the independent variable. That positive impact is a buying decision by the consumer.Keywords : location, brand image, product diversity and purchasing decision.